Analisis Perilaku Balok Beton Bertulang Tanpa Tulangan Geser Melalui Pemodelan Elemen Hingga - Muhammad Rizki; Ridwan Ridwan; Alfian Kamaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The Beam is a structural element that has the function of bearing the load perpendicular to the longitudinal axis. The collapse of reinforced concrete beams without shear reinforcement can be caused by the collapse of one of the shear force transfer components. Beams without shear reinforcement will experience changes in behavior both in terms of strength and collapse patterns. Crack patterns that occur in the test specimen due to loading can change due to changes in the shear strength of the concrete. The purpose of this study was to analyze the shear behavior of reinforced concrete beams without shear reinforcement to obtain crack patterns maximum load, and maximum deflection values through finite element model. The crack pattern of the specimens through the finite element program started by the initial cracks that initially occur in the tensile region in the form of flexural cracks, then cracks turned into diagonal cracks towards the compressive part of the beam near the load bearing which cause a failure in the form of shear failure. The results of finite element model showed the maximum load obtained by reinforced concrete beams without shear reinforcement is 31.493 kN with a deflection of 8.054 mm.Keywords: beam without shear reinforcement, FEM, shear behavior, crack pattern